The Constitutional Accommodation of Social Diversity in Nepal - Mallik, Sabita Kumari (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
This article presents the status of social diversity in Nepal and its constitutional accommodation. It reflects the multi-cultural, multi-ethnic, multi-religious, multi-lingual society and the conflicts based on their diversity, which are the major issues of Nepalese society. In multi-structured society, the diverse groups create the conflict, socio-economic tensions, autonomy movements or struggle for separations. It has originated from the prehistoric age and gradually developed with the evolution of mankind. Nepal has been struggling with some level of inequality which is the great barrier in its social and economic development. This article tries to address the major areas of social diversities which create inequalities in Nepal and its constitutional accommodation. It also focuses on the process of inclusion under the constitution, so that the diversities should be accommodated. This paper is based on multicultural and liberal theory of political science research with normative approach. The paper also used the qualitative method and secondary sources to collect information. The major thrust of this paper is to discuss about the social diversities of Nepal and its accommodation under the constitution which makes it a multicultural, multilingual, multiethnic, multi-religious country. There are various groups which are in the state of political exclusion such as indigenous, women, madhesi, dalits (the lower caste), janajati and many others. It is necessary to have representation of all these groups not only in politics but also in socio-economic sector. This paper aims to analyze the constitutional accommodation which constitutes the society in a fabric of unity in diversity.